Survey Of The Cardiovascular Drug Interactions On Geriatrics At Internal Medicine Ward Of RSUDZA Banda Aceh - Hijra Novia Suardi; Suryawati Suryawati (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
The increase of elderly population in Indonesia leads to the drug misuse. The physiological change in geriatric become the major reason. It affects the change of    drug’s pharmacodynamic, pharmacokinetics and the harmful drug interaction among overly prescribed medication. Cardiovascular drugs produce the most common side effect in elderly patient. This study aims to observe the accuracy of cardiovascular drugs used based on its dose and drug interaction. The subject of this study are the 60 years old-or more- inpatients in Rumah Sakit Umum Zainoel Abidin’s (RSUDZA) Internal medicine ward who received cardiovascular drugs prescription. The data were collected from medical record and nurse’s drugs record. The analysis were performed descriptively by evaluate the drug interaction theoritically based on literature study and available concensuses. The result shows that the Potential interaction occurred  in 75 ( 68.18 % ) of cardiovascular drug used, and 22 (20 %) of whom are important potential interactions. The most frequent drugs that have the potential interaction in this study are furosemide , spironolactone, captopril, digoxin and aspirin